Serological Frequency of Toxoplasma gondii in Domestic Cats from Shelters in Metropolitan Lima - Murdoch Quijandría, Raquel (2023)
The aim of this study was to determine the frequency of serological antibodies against Toxoplasma gondii in domestic cats (Felis silvestris catus) from shelters in Metropolitan Lima. To accomplish this, we designed a descriptive observational cross-sectional study, selecting 125 cats from shelters located in the districts of Lurin, Miraflores, and Santiago de Surco. Animals chosen were adult cats of both sexes, regardless of their health condition. They were selected proportionally and randomly within each shelter. Blood samples (1 mL) were processed using the indirect hemagglutination test to detect serological IgG and IgM antibodies against T. gondii. The frequency of IgG antibodies against T. gondii was found to be 15.2%, while the frequency of IgM antibodies againstT. gondii was 3.2%. A significant association was observed between the age of the cat and the serological frequency of T. gondii. Using the chi-square test, no association was found between the remaining characteristics of the animals under study or their epidemiological variables and the serological positivity of T. gondii.